The Role of Financial Knowledge as a Mediator in the Influence of Good Corporate Governance and Risk Management on Financial Performance in Village Credit Institutions - Maharani, Ida Ayu Dinda Priyanka; Soraya, Dewi (ProBisnis : Jurnal Manajemen, 2024)
This research aims to determine the role of financial knowledge in mediating the influence of good corporate governance and risk management on financial performance. The inconsistency of previous research results motivated researchers to add mediating variables to the research model. The mediating variable in this research is the financial knowledge variable. This research was conducted on LPDs in Badung Regency which are registered with the Badung Regency Village Credit Institution Empowerment Institute (LPPLD). The sampling procedure carried out in the research was a purposive sampling technique, namely a technique for determining samples with certain considerations. The criteria used as the basis for selecting sample members in this study were LPDs in the healthy and quite healthy categories, namely 71 LPDs. Meanwhile, the research respondents in each LPD were the Head of the LPD. The data analysis technique in this research uses the structural equation modeling (SEM) method based on partial least squares (PLS).